MC4R agonism promotes durable weight loss in patients with leptin receptor deficiency. (May 2018) - Clément, Karine; Biebermann, Heike; Farooqi, I.; Ploeg, Lex; Wolters, Barbara; Poitou, Christine; Puder, Lia; Fiedorek, Fred; Gottesdiener, Keith; Kleinau, Gunnar; Heyder, Nicolas; Scheerer, Patrick; et al.
Abstract Genetic defects underlying the melanocortin-4 receptor (MC4R) signaling pathway lead to severe obesity. Three severely obese LEPR-deficient individuals were administered the MC4R agonist setmelanotide, resulting in substantial and durable reductions in hyperphagia and body weight over an observation period of 45–61 weeks. Compared to formerly developed and tested MC4R agonists, setmelanotide has the unique capability of activating nuclear factor of activated T cell (NFAT) signaling and restoring function of this signaling pathway for selected MC4R variants. Our data demonstrate the potency of setmelanotide in treatment of individuals with diverse MC4R-related pathway deficiencies. Treatment with setmelanotide, a new-generation MC4R agonist, provides durable weight loss in hyperphagic, leptin receptor–deficient patients, suggesting a pharmacological avenue to treat patients with various MC4R pathway defects.